(untitled) (Research, Society and Development, 2023)
The concern with sustainable animal production and food competition in the production of animal feed and food for humans is a discussion that grows every day, thus, the search for alternative ingredients that can compose the diets in order to meet the nutritional requirements of animals, reducing costs and contributing to sustainable livestock production, becomes necessary. In this scenery, insects prove to be an alternative that can solve these issues, they have an ideal nutritional profile for animal nutrition, in addition to contributing to the environment, being produced with the use of a range of residues. This review aimed to address the impact of the use of insects in the diet of Japanese quails. For this, articles of different species of insects were compiled, exposing the results of these researches on parameters of zootechnical interest related to Japanese quails. We conclude that insects, example as cockroaches, beetles, crickets, moths and flies, can be used as an ingredient in these birds’ diets, replacing usual ingredients or enriching the diet, maintaining and even improving productive performance.